BUDIDAYA PADI BERAS MERAH ORGANIK DENGAN MENGGUNAKAN PUPUK BIOKOMPOS DAN BIOURIN DI DESA SENTELUK BATU LAYAR LOBAR - I Gusti Putu Muliartha Aryana; I Made Sudantha (Jurnal Abdi Insani, 2022)
This community service activity aims to 1). Increase the knowledge and skills of partner farmers in farming techniques for organic brown rice upland rice 2). Partner farmers will be able to produce organic fertilizers in the form of biocompost and biorin using cow dung and animal feed scraps using fermentation technology using Tricoderma spp. The method to be used in this PkM program is a training method followed by field practice work and active participatory action research in the field from preparation to evaluation. The activities were carried out at the Putra Gembala farmer group for the production of biocompost and biourin and the Harapan II Farmers Group for the practice of cultivating organic red upland rice. By involving 10 group members. Conclusion: 1. There was an increase in knowledge and skills of the Harapan II farmer group and the Putra Gembala farmer group in the cultivation of organic brown rice upland rice in dry land using solid organic fertilizer (Biokompos) and liquid organic fertilizer (biourin) Trichoderma sp from cow manure waste.